2011
DOI: 10.1097/ico.0b013e3181dc8184
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Acellular Porcine Corneal Matrix Using Sodium Dodecylsulfate

Abstract: A simple and valid method to produce decellularized corneal matrix has been successfully developed. These acellular matrices similar to natural corneas in structure, strength, and transparency have tremendous potential for corneal transplantation as ideal implants for donors and for tissue engineering applications as suitable scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 35 publications
0
35
0
1
Order By: Relevance
“…Alternatively, efforts by a number of investigators have focused on the use of de-cellularized, chemically-treated pig corneas as an alternative to human donor corneal tissue [10][11][12][13]. While this approach has shown promising results in animal models, the standardized procurement, decellularization methods, storage procedures, and material certification for human use are lacking and can lead to varying outcomes, for example with respect to transparency of the final constructs [10,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, efforts by a number of investigators have focused on the use of de-cellularized, chemically-treated pig corneas as an alternative to human donor corneal tissue [10][11][12][13]. While this approach has shown promising results in animal models, the standardized procurement, decellularization methods, storage procedures, and material certification for human use are lacking and can lead to varying outcomes, for example with respect to transparency of the final constructs [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…The surgery minimizes disturbance of the epithelium and maintains corneal shape and curvature without suturing, thereby avoiding stimulation of an aggressive wound healing response. Additionally, FLISK can be considered a therapeutic procedure for replacement of diseased or damaged native stroma, in contrast to micropocket insertion models [10,12,13] where native tissue is not excised thus leading to an unnatural refraction and stromal architecture, inflammation, and the need for surgical suturing and use of postoperative steroids. In this study, it was found that the BPC implants maintained the shape and structure of the host cornea while supporting rapid healing and a limited in-growth of host stromal cells, which began to degrade the implanted collagen scaffold and produce new host collagen in less than 8 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…21 In the cornea, decellularized xenograft matrices have been studied primarily for stromal replacement. [22][23][24][25][26][27][28] In this study, we undertook a tissue-engineering approach to evaluate methods for removing cells from human cadaver corneas while maintaining the integrity of the basement membrane and the stromal matrix. The optimized protocol resulted in a decellularized cornea fully capable of supporting the growth and differentiation of human corneal epithelial and stromal cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…fibres and matrix. Parameter E can be used to describe the combined response of the corneal fibres and matrix (Dunn andSilver 1983, Edmund 1988), whereas when appropriately transformed, and τi can describe corneal matrix behaviour (Dunn and Silver 1983, Crabb et al 2006, Zhou et al 2011.…”
Section: Methodsmentioning
confidence: 99%